Stress Sensitivity Analysis of the Beam and Shell Finite Elements - Milan Saga; Milan Vasko (Communications - Scientific letters of the University of Zilina, 2009)
The stress sensitivity analysis in conjunction with finite elements method represents an important tool for the influence analysis of the structural parameters. This analysis plays a significant role in the decision process of the formulation of the structural optimizing or probability analysis. The goal of the paper is to present theoretic and numerical aspects of the beam and shell element stress sensitivity analysis with the respect to the cross section parameters (cross section area, thickness, etc.). The whole computational procedure was inbuilt into Matlab’s software module MATFEM.